PENINGKATAN KAPASITAS PENGELOLA ZAKAT MELALUI PELATIHAN AKUNTANSI ZAKAT MENUJU AKUNTABILITAS PUBLIK KOTA LHOKSEUMAWE - Fuadi, Fuadi; M. Nur, Mukhlis; Falahuddin, Falahuddin; Arliansyah, Arliansyah; Wahyuddin, Wahyuddin; Khairawati, Khairawati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2022)
The goal to be achieved in this PKM is to increase the capacity of Zakat managers in Lhokseumawe City in presenting ZIS fund management reports based on PSAK 109 in a transparent and accountable manner, so that the reports presented can be understood by muzzaki and practitioners and academics can be used as a reliable source of public information. . The method used to improve understanding of ZIS accounting based on PSAK 109 is participatory-based learning. Participatory is meant to be learning activities and direct learning of active involvement in the process of a particular program or activity in various stages starting from involvement in planning, implementing, monitoring and evaluating programs/activities by the PKM team and partners. At the end of the PKM program, partners are expected to be able to carry out accounting processes starting from recognition, measurement, recording and presentation as well as financial reporting in accordance with PSAK 109 accounting standards regarding generally accepted accounting for zakat, infaq, and alms.